Percutaneous absorption of uranium compounds - Molinari de Rey, Beatriz L.; Lanfranchi, Héctor E.; Cabrini, Rómulo Luis (Academic Press Inc. (London) Ltd., 1983)
Fil: Molinari de Rey, Beatriz L. Comisión Nacional de Energía Atómica; Argentina